Emergent food proteins – Towards sustainability, health and innovation. (November 2019) - Fasolin, L.H.; Pereira, R.N.; Pinheiro, A.C.; Martins, J.T.; Andrade, C.C.P.; Ramos, O.L.; Vicente, A.A.
Abstract: There is an increasing demand for alternative and sustainable protein sources, such as vegetables, insects and microorganisms, that can meet the nutritional and sensory pleasantness needs of consumers. This emergent interest for novel protein sources, allied with "green" and cost-effective processing technologies, such as high hydrostatic pressure, ohmic heating and pulsed electric fields, can be used as strategies to improve the consumption of proteins from sustainable sources without compromising food security. In addition to their nutritional value, these novel proteins present several technological-functional properties that can be used to create various protein systems in different scales (i.e., macro, micro and nano scale), which can be tailored for a specific application in innovative food products. However, in order for these novel protein sources to be broadly used in future food products, their fate in the human gastrointestinal tract (e.g., digestion and bioavailability) must be assessed, as well as their safety for consumers must be clearly demonstrated. In particular, these proteins may become novel allergens triggering adverse reactions and, therefore, a comprehensive allergenicity risk assessment is needed. This review presents an overview of the most promising alternative protein sources, their application in the production of innovative food systems, as well as their potential effects on human health. In addition, new insights on sustainable processing strategies are given. Graphical abstract: Unlabelled Image Highlights: Sustainable aspects of alternative proteins (vegetables, insects and microbial) are explored. Eco-innovative food processing technologies effects on protein properties are reviewed. New proteins sources as ingredients are still little explored, mainly in micro and nanoscales. Allergenicity and toxicity assessment of emergent proteins is of utmost importance.